Cesarean hysterectomy at the Maria Auxiliadora Hospital - Orderique, Luis (2015)
OBJECTIVE: To evaluate frequency, indications and repercusions of cesarean hysterectomy. DESIGN... Descriptive retrospective study of cases attended at Lima Maria Auxiliadora Hospital between july 1988 and june 1997. RESULTS: Of 47427 deliveries 314 ended in cesarean hysterectomy (0,7916), more frequently between 20 and 35 year-old (66,8916) and similar percentages at extreme ages (16,5910). Primiparae represented 45,2%, more frequently between 37 and 41 weeks gestation. Frequent maternal pathologies were PROM, anemia, preeclampsia, UTI, 7TH, STH, TPL. IUGR was 19,7916, prematurity 15,9%, intermediate fetal mortality 59,8 x 1000 lb, latefetal mortality 156,4, perinatal mortality 173,9 and maternal mortalit 3347x 100000 lb.